Investigation of lead exposure awareness of families with children aged 0-6 who applied to a district polyclinic - Duygu Akçay; Lütfiye Hilal Özcebe (Turkish Journal of Public Health, 2018)
Objective: This study was conducted to investigate lead exposure awareness of families with children aged 0-6, who applied to a district polyclinic. Method: The research was carried out in Hüseyin Savaş district clinic between the 11th-21st of October, 2016. Amongst all the parents who applied to the polyclinic over the given time period, a questionnaire was administered to 101 parents who volunteered to participate. The questionnaire was created by using the literature and was administered through the face-to-face survey application technique. Results: It was determined that 86.1% of the participants did not have sufficient knowledge of lead poisoning. The mean score on the lead poisoning prevention awareness scale was lower for mothers with a high school education, when compared to those with university degrees. Furthermore, the mean score for prevention awareness was higher for respondents living in the centre of the province, compared to those from peripheral villages and towns. In addition, participants with higher economic status perceptions were found to be more knowledgeable than those with moderate perceptions. Conclusion: More education for parents, caregivers and children about lead exposure will raise awareness about the issue.